The Role of E-Government Innovation in Enhancing Public Service Performance and Strengthening Transparent ‎Governance - Wirata, Gede; Gunawan, Mohamad Sigit; Judijanto, Loso; Sarmento, Amândio de Araújo; Permono , Arkanudin Rizki (International Journal of Accounting and Economics Studies, 2025)
This study investigates the role of e-government innovation in enhancing public service performance and strengthening transparent ‎governance. Through a comprehensive literature review, the research explores how digital platforms improve service delivery, reduce ‎bureaucratic delays, and foster greater citizen engagement. The findings reveal that e-government systems significantly enhance the ‎efficiency and accessibility of public services, as demonstrated by faster processing times and increased citizen satisfaction in countries such ‎as Estonia and South Korea. Moreover, the research highlights the positive impact of e-government on governance transparency, where real-time data sharing and open government initiatives have improved public trust and reduced corruption. However, challenges such as ‎inadequate infrastructure, limited digital literacy, and data privacy concerns pose significant barriers to the successful implementation of e-government, particularly in developing countries. The study underscores the importance of digital inclusion and robust cybersecurity ‎measures to ensure that all citizens benefit equally from e-government systems. The findings contribute to the growing body of knowledge ‎on e-government by offering valuable insights into its role in enhancing public service performance and transparency. Future research ‎should focus on the long-term sustainability of e-government, the integration of emerging technologies like artificial intelligence and ‎blockchain, and the overcoming of barriers in resource-constrained environments‎.